Sodium-Dependent Glucose Transporter Type 2 Inhibitors as a Breakthrough in Neutropenia and Neutrophil Dysfunction Management in Patients with Glycogen Storage Disease Type Ib - Andrey N. Surkov; Leyla S. Namazova-Baranova; Anna L. Arakelyan; Evgeny E. Bessonov; Natalia V. Zhurkova (Вопросы современной педиатрии, 2024)
Glycogen storage disease type Ib (GSD Ib) is a rare and extremely severe disease included in the group of hereditary carbohydrate metabolism disorders. The condition is caused by pathogenic variants in the SLC37A4 gene leading to glucose metabolic disorder in the liver and kidneys, and as a result to severe organomegaly, hypoglycemia, and metabolic decompensation. Moreover, neutropenia and neutrophil dysfunction are noted in patients with GSD Ib. The use of granulocyte colony stimulating factor only increases the number of dysfunctional neutrophils without affecting their functional activity, what determines the inefficacy of such treatment. In recent years, the mechanism of neutropenia in GSD Ib has been clarified, so new therapeutic agents for its relief have been created. This article presents the overview of data on the successful results of renal sodium-glucose cotransporter type 2 inhibitors (gliflozins) usage in patients with GSD Ib.